Evolutionary management of coral‐reef fisheries using phylogenies to predict density dependence. Issue 7 (11th August 2021) - Houk, Peter; Lemer, Sarah; Hernandez‐Ortiz, Dalia; Cuetos‐Bueno, Javier
Abstract: Harvesting models are based upon the ideology that removing large, old individuals provides space for young, fast‐growing counterparts that can maximize (fisheries) yields while maintaining population stability and ecosystem function. Yet, this compensatory density dependent response has rarely been examined in multispecies systems. We combined extensive data sets from coral‐reef fisheries across a suite of Pacific islands and provided unique context to the universal assumptions of compensatory density dependence. We reported that size‐and‐age truncation only existed for 49% of target coral‐reef fishes exposed to growing fishing pressure across a suite of Pacific islands. In contrast, most of the remaining species slowly disappeared from landings and reefs with limited change to their size structure (i.e., little to no compensation), often becoming replaced by smaller‐bodied sister species. To understand these remarkable and disparate differences, we constructed phylogenies for dominant fish families and discovered that large patristic distances between sister species, or greater phylogenetic isolation, predicted size‐and‐age truncation. Isolated species appeared to have greater niche dominance or breadth, supported by their faster growth rates compared to species with similar sizes and within similar guilds, and many also have group foraging behavior. In contrast, closely related species may have more restricted, realized niches that led to their disappearance and replacement. We conclude that phylogenetic attributes offered novel guidance to proactively manage multispecies fisheries and improve our understanding of ecological niches and ecosystem stability.